A voice and nothing more - Dolar, Mladen (Cambridge, Mass. : MIT Press, 2006)
The voice was not a major philosophical topic until the 1960s, when Derrida and Lacan separately proposed it as a central theoretical conce rn. Here, Dolar goes beyond Derrida's idea of "phonocentrism" and reviv es and develops Lacan's claim that the voice is one of the paramount em bodiments of the psychoanalytic object. He proposes that, apart from th e uses of the voice as a vehicle of meaning and as a source of aestheti c admiration, there is a third level of understanding: the voice as an object that can be seen as the lever of thought. He investigates the ob ject voice on a number of different levels--linguistics, metaphysics, e thics (the voice of conscience), the paradoxical relation between the v oice and the body, the politics of the voice--and finally scrutinizes t he uses of the voice in Freud and Kafka. With this foundational work, D olar gives us a philosophically grounded theory of the voice as a Lacan ian object-cause.--From publisher description.
Includes bibliographical references (p. [189]-[214]) and index.
Keywords: Voice (Philosophy)